1949
DOI: 10.1021/ja01179a004
|View full text |Cite
|
Sign up to set email alerts
|

A Synthesis of Vinylcyclopropane

Abstract: A Synthesis of Vinylcyclopropane 3595 bers indicate some molecular freedom below the freezing point, but no Maxwell-Wagner polarization due to conductivity was encountered in the cases of the three longer molecules. The dielectric properties of the alcohols and amines have been compared, and tentative reasons advanced for the absence of the rotator state in the amines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

1967
1967
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 0 publications
1
18
0
1
Order By: Relevance
“…The polymerizability of VCP with dibenzoyl peroxide (DBPO) and with ultraviolet radiation was reported for the first time in 1949 9) . Some years later, the cationic homopolymerization of VCP and its radical copolymerization with butadiene, styrene, or methyl methacrylate was the subject of two US patents 62,63) .…”
Section: Polymerization Of Vinylcyclopropane and Monosubstituted Derimentioning
confidence: 99%
See 1 more Smart Citation
“…The polymerizability of VCP with dibenzoyl peroxide (DBPO) and with ultraviolet radiation was reported for the first time in 1949 9) . Some years later, the cationic homopolymerization of VCP and its radical copolymerization with butadiene, styrene, or methyl methacrylate was the subject of two US patents 62,63) .…”
Section: Polymerization Of Vinylcyclopropane and Monosubstituted Derimentioning
confidence: 99%
“…Although the polymerization of VCP was already described in 1949 9) , the interest in the polymerization of VCPs has grown recently [10][11][12] , for example, as lowshrinking monomers in photopolymerization systems or for dental applications.…”
Section: Introductionmentioning
confidence: 99%
“…10' O s-', respectively [24]. Ethylcyclopropane (37) was synthesized via Wolff-Kishner reduction of l-cyclopropylethanone [25]. It reacted in 21% yield to afford 40; only unreacted 37, but no products derived from 39 were detected in the reaction mixture.…”
Section: Optimization Of Reaction Conditionsmentioning
confidence: 99%
“…Many of these studies, however, have utilized results from ultraviolet spectroscopic studies, for which i t is not possible to decide if the observed changes attributed to cyclopropyl conjugation arise from interactions in the ground state or an excited state (or both). Other techniques which do not suffer from this difficulty have been employed for the same purpose, including infrared (8) and Raman (9) spectra, dipole moment measurements (lo), exaltation of molecular refraction ( l l ) , heats of combustion data (12), boiling point differences (13), and, more recently, proton spectra of cationic species (14) For personal use only.…”
Section: Introductionmentioning
confidence: 99%